PERAN ACCOUNT OFFICER DI LEMBAGA KEUANGAN SYARI’AH (Studi Kasus di BMT Citra Mandiri Syari’ah Jepara) - Riyadi, Fuad; Wahyuni, Sri (IAIN Kudus, 2017)
Account officer has a very important role. This role will affect the level of profit earned by a financial institution. This is because the handler of transactions that occur between the customer and the Financial Institution is in the hands of the account officer. This study aims to analyze the role of account officer in BMT Citra Mandiri Syariah in Jepara. The research data were collected through interviews with the respondents. The results of this study indicate that the role of account officer especially in BMT Citra Mandiri Syariah Jepara is very important. This role can ultimately affect the level of profit to be gained. This is because the role of account officer who handles transactions between customers with financial institutions, including the process of financing problem settlement. In the long run the role of account officer can affect the level of cutomer loyalty.Keywords:role,account officer,loyalty